2012
DOI: 10.1111/j.1365-2966.2012.20647.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of galactic discs: finite arm-inclination and finite-thickness effects★

Abstract: A modified theory of the Lin–Shu density waves, studied in connection with the problem of spiral pattern of rapidly and differentially rotating disc galaxies, is presented for both the axisymmetric and non‐axisymmetric structures in highly flattened galaxies resulted from the classical Jeans instability of small gravity perturbations (e.g. those produced by a spontaneous disturbance). A new method is provided for the analytical solution of the self‐consistent system of the gas‐dynamic equations and the Poisson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 89 publications
(213 reference statements)
4
33
0
Order By: Relevance
“…The gravitational instability criterion for nonaxisymmetric perturbations contains a factor α, which for the one-fluid case range from ≈ 1/3 (Hunter et al 1998) to ≈ 1/2 (Kennicutt 1989;Martin & Kennicutt 2001). The corresponding star formation threshold Q g < 2 − 3 also follows from the theoretical (Morozov 1985;Griv & Gedalin 2012) and numerical (Li et al 2005) investigations. Also there are some evidences of even a higher level of instability (Q g < 2 − 4 in Zasov & Zaitseva 2017 and Q RW ≈ 1 − 4 in star-forming spirals from THINGS, see figure 5 in Romeo & Wiegert 2011).…”
Section: Instability Levelsmentioning
confidence: 83%
“…The gravitational instability criterion for nonaxisymmetric perturbations contains a factor α, which for the one-fluid case range from ≈ 1/3 (Hunter et al 1998) to ≈ 1/2 (Kennicutt 1989;Martin & Kennicutt 2001). The corresponding star formation threshold Q g < 2 − 3 also follows from the theoretical (Morozov 1985;Griv & Gedalin 2012) and numerical (Li et al 2005) investigations. Also there are some evidences of even a higher level of instability (Q g < 2 − 4 in Zasov & Zaitseva 2017 and Q RW ≈ 1 − 4 in star-forming spirals from THINGS, see figure 5 in Romeo & Wiegert 2011).…”
Section: Instability Levelsmentioning
confidence: 83%
“…Note that Qcrit is higher than unity, but its precise value is still questioned (Romeo & Fathi 2015). In fact, Qcrit is influenced by complex phenomena such as non-axisymmetric perturbations (e.g., Griv & Gedalin 2012) and gas dissipation (Elmegreen 2011), whose effects are difficult to evaluate. Now that we have clarified how self-regulated galaxy discs are, let us analyse how the Toomre parameter of component i, Qi = κσi/πGΣi, varies from galaxy to galaxy.…”
Section: The Big Picturementioning
confidence: 99%
“…Unfortunately, there is still no general consensus about the value of Qcrit. For example, Griv & Gedalin (2012) found that the classical estimate Qcrit ≈ 2 is an absolute upper limit on the critical stability level. Elmegreen (2011) showed that gas dissipation has a similar destabilizing effect, and estimated that Qcrit ≈ 2-3.…”
Section: Highly Non-trivial Aspects Of the Problemmentioning
confidence: 99%